Synchronic Analysis of Keris in Citizenship Social Class Stratification - Hudjolly Hudjolly; Siti Inayatulloh (Budapest International Research and Critics University, 2022)
The Indonesian treasures civilization have known keris for 1000 years ago until the time of independence. Keris is often mentioned in the counter-colonialism narration led by royal figures, aristocrats such as keris of Prince Diponegara's, keris kyai naga siluman luk 13 and kyai nagasiluman luk 11 owned by the Sultan of Yogyakarta. The keris contains a widely adopted the pakem as symbolic framework. Obedience to the pakem implies a political citizenship, such as kyai carubuk kris, kyai kalamunyeng, mahesalanjer, jalatunda. Pakem keris also has a series of symbols that are accepted by the public and accepted individually, such as ladrang, dhapur, pamor. The materials of the keris, starting from the type of wood, the type of metal for the bilah (body of blade’s), the form of carving the keris upstream, the warangka and its ornaments refer to a certain social class stratification as well as a marker of one's capacity. Keris becomes self-representative, represents individual identity and to gain recognition in the community. This study analyzes the keris symbol which is used as a class arrangement and civic politics which is diachronic type. The results of the diachronic analysis show that the division of social classes does not always refer to the class divisions of Max Weber and Marx's version.